Dance Education as Social Studies Education - Susan R. Koff (Center for Educational Policy Studies Journal, 2025)
Measurement of formal education success excludes arts education and focuses instead on reading, mathematics and science. In a world filled with differences between people, geography, backgrounds, customs, religions and sense of self, the only subject that approaches this knowledge is social studies. This discipline is not tested in the Programme for International Student Assessment, but is tested tangentially in the United States. In general, consideration of separate subjects in formal schooling does not encourage focus on what creates the holistic human beings who occupy this complex world. Within the United States, social studies emphasises citizenship and participation in democracy. The purpose of this article is to clearly articulate how dance education, a comprehensive education that enables young people to work in and encounter the world around them, can include social studies. An online survey of dance education practitioners results in ideas that cannot be implemented through the efforts of dance education alone, but require education policy decisions to enable implementation.